Algunos hongos hipogeos de Andorra - Vidal i Frigola, Josep Maria; Vila i Garcia, Jordi (Revista Catalana de Micologia, 2007)
Some hipogeous fungi from Andorra. The hypogean mycoflora of Andorra is studied for the first time. In this work, five especies of hypogeous fungi are studied; three of them are new records for the Iberian Peninsule flora: Endogone pisiformis, - Tuber rapaeodorum and Leucophlebs aculeatispora,a rare species from Europe.